Drug Delivery: Biodegradable Passion Fruit‐Like Nano‐Architectures as Carriers for Cisplatin Prodrug (Part. Part. Syst. Charact. 11/2016). (15th November 2016) - Cassano, Domenico; Santi, Melissa; Cappello, Valentina; Luin, Stefano; Signore, Giovanni; Voliani, Valerio
Abstract : The clinical translation of inorganic nanoparticles (NPs) requires combining the feasibility of body clearance typical for ultrasmall NPs with the physical behavior of bigger NPs. On page 818, V. Voliani and co‐workers present passion fruit‐like nano‐architectures: this novel approach to the synthesis of nanoparticles results in nanocapsules that degrade to kidney‐clearable building blocks after their therapeutic or diagnostic action.